KOSAKATA MAKANAN TRADISIONAL YANG BERBAHAN TAEK LALAK PADA MASYARAKAT MELAYU SAMBAS - Asrica, Wirit; Syahrani, Agus; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research discusses the form of lingual units, lexical meanings and grammatical meanings found in traditional food made from taek lalak in Tri Kembang Village, Sambas Regency, then implemented in procedural text material for class VII of the Merdeka Curriculum. The aim of this research is to identify lexical forms related to tools, ingredients, how to make and how to serve traditional food made from taek lalak and then describe them using descriptive methods in qualitative form. The data source in this research is the people of Tri Kembang Village who speak the Sambas Dialect Malay Language (BMDS). Data collection techniques in this research used observation and interview techniques. This research produced 75 forms of lexicon, in the form of 16 tool lexicons, 23 material lexicons, 28 how to lexicons, and 8 how to lexicons. The lexical meanings identified in this study based on the form of lingual units found 42 monomorphemic forms, 19 polymorphemic forms, and 14 phrase forms. The grammatical meaning identified in this research has 1 data related to the tools used, 14 data related to the materials used, 14 data related to how to make it, and 4 data related to how to present it.